2014
DOI: 10.1158/1078-0432.ccr-14-0770
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Perifosine and Sorafenib Dual-Targeted Therapy in Patients with Relapsed or Refractory Lymphoproliferative Diseases

Abstract: Purpose: To evaluate safety and activity of perifosine and sorafenib combination therapy in patients with lymphoproliferative diseases.Experimental Design: Patients with relapsed and refractory lymphoproliferative diseases received perifosine (50 mg twice daily) for 1 month. Patients achieving less than partial response (PR) after perifosine alone were administered the combination therapy [perifosine plus sorafenib (400 mg twice daily)] until progressive disease (PD) or unacceptable toxicity occurred. The pERK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Nevertheless, additional combinations of perifosine with current therapeutic drugs are still in progress. In this regard, a phase II clinical trial using perifosine and sorafenib combination therapy showed some promising results with manageable toxicity in patients with Hodgkin lymphoma (Guidetti, et al, 2014). In addition, a phase II clinical trial of perifosine and Torisel (temsirolimus) in patients with recurrent/progressive malignant glioma to determine the induction of tumor shrinkage or stabilization and/or a delay in disease progression (NCT02238496) (Andrew Lassman, Columbia University; Pfizer; AEterna Zentaris) is underway.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, additional combinations of perifosine with current therapeutic drugs are still in progress. In this regard, a phase II clinical trial using perifosine and sorafenib combination therapy showed some promising results with manageable toxicity in patients with Hodgkin lymphoma (Guidetti, et al, 2014). In addition, a phase II clinical trial of perifosine and Torisel (temsirolimus) in patients with recurrent/progressive malignant glioma to determine the induction of tumor shrinkage or stabilization and/or a delay in disease progression (NCT02238496) (Andrew Lassman, Columbia University; Pfizer; AEterna Zentaris) is underway.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In in vivo xenograft studies there was a reduction in tumor burden, increased survival, and enhanced tumor cell killing produced by this combination compared with single agents (Locatelli et al, 2013). A recent study also evaluated the combination in patients with lymphoproliferative diseases (Guidetti et al, 2014; Table 1). Patients who had received single-agent perifosine for relapsed and refractory lymphoproliferative diseases, and who achieved less than a partial response, received the combination therapy until the disease progressed or toxicity was unacceptable.…”
Section: Development Of Drug Combinations Containing Alpsmentioning
confidence: 99%
“…Initial results supported a clinical response in 7 of 25 patients with Hodgkin lymphoma. Also promising, 4 of 8 patients with chronic lymphocytic leukemia responded to perifosine alone (Guidetti et al, 2014). The clinical responses observed in the patients with relapsed and refractory Hodgkin lymphoma suggest that this subgroup could serve as target population for new studies (Guidetti et al, 2014).…”
Section: Development Of Drug Combinations Containing Alpsmentioning
confidence: 99%
“…These findings were dependent on potent, early, time‐dependent ROS generation. Taken together, these data suggest that Givinostat/Sorafenib treatment warrants attention in refractory/relapsed HL patients .…”
Section: Strategies For Therapeutic Targeting Of Primary Refractory Amentioning
confidence: 99%